2007
DOI: 10.21273/jashs.132.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Ethylene and Color Development in the Skin of ‘Pink Lady’ Apple

Abstract: To elucidate the temporal relationship between endogenous ethylene and color development, changes in ethylene concentration, fruit color, pigments, and flavonoids were monitored at different intervals during the development and ripening of ‘Pink Lady’ apple (Malus × domestica Borkh.), commencing from 60 days after full bloom (DAFB) in 2002 to 2003, and 7 DAFB in the 2003 to 2004 season. Concentrations of chlorogenic acid, phloridzin, catechin, epica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 26 publications
6
54
0
1
Order By: Relevance
“…In this study, about 85% of changed proteins and 38% of up-regulated mRNA in ALA-treated apple skin have a secondary function associated with fruit ripening (Figure 3C and Table 2). This result is not surprising because most fruits accumulate anthocyanin only in their ripening phase (Jaakola et al, 2002; Whale and Singh, 2007; Negri et al, 2008; Bureau et al, 2009). Our results demonstrate that ALA regulates the expression of ripening-related genes and therefore provide more evidence on the regulation of fruit ripening by ALA.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, about 85% of changed proteins and 38% of up-regulated mRNA in ALA-treated apple skin have a secondary function associated with fruit ripening (Figure 3C and Table 2). This result is not surprising because most fruits accumulate anthocyanin only in their ripening phase (Jaakola et al, 2002; Whale and Singh, 2007; Negri et al, 2008; Bureau et al, 2009). Our results demonstrate that ALA regulates the expression of ripening-related genes and therefore provide more evidence on the regulation of fruit ripening by ALA.…”
Section: Discussionmentioning
confidence: 96%
“…The central role of ethylene in apple fruit ripening has been well-studies (Dandekar et al, 2004; Schaffer et al, 2007). Of these, ethylene appeared to be a key factor regulating anthocyanin biosynthesis and color development in apple fruit (Whale and Singh, 2007). In the present study, we also identified 1-aminocyclopropane-1-carboxylate oxidase 1 (ACO1, No.…”
Section: Discussionmentioning
confidence: 99%
“…, 2002; Whale & Singh, 2007). Ethylene production is positively correlated to red blush development and accumulation of total anthocyanins in the skin of ‘Cripps Pink’ apple fruit (Whale & Singh, 2007). Furthermore, the development of red blush in apple fruit has been reported to be down and up‐regulated with the exogenous application of AVG (ethylene inhibitor) or ethephon (ethylene promoter), respectively (Whale et al.…”
Section: Introductionmentioning
confidence: 98%
“…The development of red blush on the apple fruit is regulated by accumulation of various anthocyanins and carotenoids (Lancaster, 1992; Awad & De Jager, 2002; Whale & Singh, 2007). These secondary metabolites contain various anti‐oxidative, anti‐microbial, anti‐mutagenic and anti‐carcinogenic properties, and contribute to both fruit colour as well as being beneficial to human health (Awad & De Jager, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation